폐자원을 이용한 사격장 토양내 중금속(Pb, Cu) 안정화 처리 - 이근영(Keun Young Lee); 문덕현(Deok Hyun Moon); 김경웅(Kyoung Woong Kim); 정경훈(Kyung Hoon Cheong); 김태성(Tae Sung Kim); 김지형(Jee Hyeong Khim); 문경란(Kyoung Ran Moon); 최수빈(Su Bin Choi) (Daehan hwan'gyeong gonghag hoeji, 2011)
In this study, a heavy metal stabilization treatment using waste resource stabilizing agents was utilized on army firing range soil contaminated with Pb and Cu. Both calcined oyster shells (COS; 5% w/w) and waste cow bone (WCB; 3% w/w) were applied for a wet-curing duration of 28 days. Following the stabilization treatment, the process efficiency was evaluated by various extraction methods for Pb and Cu. Neutral and weak acid extraction methods, such as water soluble extraction and SPLP, did not show positive results for heavy metal stabilization with very low leachability. On the other hand, TCLP and 0.1 N HCl extraction showed that the stabilizing agents significantly reduced the amount of the heavy metals leached from the soil, which strongly supports that the treatment efficiency is positively evaluated in acidic leaching conditions. Specifically, in the 0.1 N HCl extraction, the reduction efficiencies of Pb and Cu leaching were 99.9% and 83.9%, respectively. From the sequential extraction results, a difference between Pb and Cu stabilization was observed, which supports that Pb stabilization is more effective due to the formation of insoluble Pb complexes. This study demonstrates that the application of waste resources for the stabilization of heavy metals is feasible. 본 연구는 Pb와 Cu로 오염된 사격장 토양을 대상으로 폐자원을 가공하여 만든 안정화제를 이용하여 안정화 처리를 수행하였다. 안정화제는 폐굴껍질을 소성하여 생석회로 가공한 Calcined oyster shells (COS)와 폐소뼈를 가공한 Waste cow bones (WCB)로 오염토 함량대비 각각 5%와 3%를 사용하여, 28일간 습윤양생한 후 각종 용출시험법을 통해 효율성을 평가 하였다. 증류수 용출 및 SPLP에서는 뚜렷한 안정화 효율이 관찰되지 않았는데, 이는 중성 또는 약산성 환경에서는 중금속의 용출량 자체가 많지 않기 때문으로 판단된다. 반면, TCLP 및 0.1 N HCl을 이용한 용출실험에서는 안정화 처리를 한 토양의 경우 중금속의 용출량이 확연하게 감소한 것을 확인할 수 있었다. 특히, 0.1 N HCl 용출 결과에서 Pb 99.9%, Cu 83.9%의 매우 높은 용출량 저감효과를 보였고, 이는 비교적 강산성 용출환경에서는 중금속의 안정화 효과가 크게 나타남을 의미한다. 연속추출 결과를 통해 Pb와 Cu 간에 안정화 경향성의 차이는 Pb가 불용성 물질로의 변환과 안정화 효율이 더 탁월한 것으로 판단된다. 본 연구는 폐자원을 이용한 안정화제가 오염토양 처리에 활용 가능함을 증명하고 있고, 또한 폐기물로 취급되는 폐자원의 재사용 방안을 제시한다는 점에서도 큰 의미를 갖는다.